Vernon-Wager papers - Vernon, Edward, 1684-1757.
Correspondence of Vernon and Sir Charles Wager (1666-1743), British admirals, relating to English operations in the West Indies, the naval expedition against Cartagena, Colombia and Cuba, a proposed expedition against Georgia and Florida, attempts to suppress piracy on the Spanish Main, the slave trade, the commercial operations of the South Sea Company, Jamaica, the Bahamas, and the Philippines. Correspondents include Sir Jeffery Amherst, Martin Bladen, Lt. Gov. Francis Fauquier, Major Gen. Thomas Gage, Lt. Gov. Charles Lawrence, Sir John Norris, Andrew Stone, Sir Edward Trelawny, James O'Hara Tyrawly, and Maj. Gen. Thomas Wentworth.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
British naval officer.
Calendar published by the Library of Congress, 1904. Finding aid available in the Library of Congress Manuscript Reading Room.
Forms part of: Peter Force papers and collection (Series 8D : entry 181).
Keywords: Amherst, Jeffery Amherst, -- Baron, -- 1717-1797 -- Correspondence; Bladen, Martin, -- 1680-1746 -- Correspondence; Fauquier, Francis, -- 1704?-1768 -- Correspondence; Gage, Thomas, -- 1721-1787 -- Correspondence; Lawrence, Charles, -- 1709-1760 -- Correspondence; Norris, John, -- Sir, -- 1660?-1749 -- Correspondence; Stone, Andrew, -- 1703-1773 -- Correspondence; Trelawny, Edward, -- 1699-1754 -- Correspondence; Tyrawly, James O'Hara, -- Baron, -- 1690-1773 -- Correspondence; Wager, Vernon -- Correspondence; Wentworth, Thomas -- Correspondence; Great Britain. -- Royal Navy -- Foreign service -- North America; Great Britain. -- Royal Navy -- Foreign service -- West Indies; South Sea Company; Pirates -- Spanish Main; Slave trade; Bahamas -- Commerce; Colombia -- History; Cuba -- History; Great Britain -- History, Naval; Jamaica -- Commerce; Philippines -- Commerce; West Indies -- History, Naval; Naval officers, British